The Discourse of ADHD Perspectives on Attention Deficit Hyperactivity Disorder - Horton-Salway, Mary (The Language of Mental Health, 2018)
This book explores the discourse of attention deficit hyperactivity disorder (ADHD), one of the most debated mental health categories attributed to children and adults across the globe. The authors trace the origins, development and representation of ADHD to demonstrate how the category is produced through competing explanatory theories and processes of scientific, professional and lay discourse. Starting with the idea that medical categories are as much a product of cultural meaning, social processes and models of medicine as they are of scientific fact, this book utilises a range of perspectives from within critical discursive psychology to approach this topic. The authors discuss historical construction, media representation, parents' accounts of family life, and the personal experience of children and adults to demonstrate how the construction of social identity and cultural stereotypes are embedded in the meaning of ADHD. They explore the origins of ADHD and how biological and psychosocial explanations of the mental health category have been produced, circulated, debated and resisted within a culture of 'Othering', and the discourse of blame. .